Inverted Archetypes: A Comparative Study of the Foundation Myths of two Southeast Moluccan Societies - Howes, David (Culture, 1987)
This essay describes the ways in which two eastern Indonesian societies move meaning in different directions so as to distinguish themselves from each other. An attempt is made to uncover the laws of this motion, and thus account for the particular form which each society takes. It is shown that the differences between the societies of the Kei and Tanimbar Islands may be enucleated in terms of the operation of a limited set of laws or principles of collective ideation, such as inversion, opposition and invagination.